PRODUCTIVE CHAIN OF THE GINGER (Zingiber officinale ROSCOE) ON PARANA STATE: ANALYSIS AND RECOMMENDATIONS TO IMPROVEMENT FROM QUALITY - Elpo, Eliane Rose Serpe; Negrelle, Raquel Rejane Bonato (Scientia Agraria, 2006)
Prospective studies of the productive chain of the Zingiber officinale Roscoe on Parana State identifying the main agents envolved and parallel procedure analysis of the strangulation points, in order to microbiology quality this product in whole levels from the production until commercialization last phase, aiming identify causes and propose solutions to the improvement of the system in general. This survey developed from 2000 to 2002 involved field research, interviews with representative of the commercialization establishments, producers and others actors of the productive chain, besides made in laboratories of the quality of crude product available to the consumer market in Curitiba. This paper is organized in nine chapters that present information involving botanical, ecological, physiquechemical and pharmacological aspects of ginger that are included in chapters 1 and 2. The chapter 3 presents the characteristics of the main brazilian productive area, embody localization, social and economic aspects, geologycal, geomorphologycal and climate characterization. The chapter 4 the study of the productive chain of this product in Parana State, which includes the paranaense, the brazilian and the worldwide panoramic view of the production volume and commercialization of the ginger; characterization of the agricultural community; identification and characterization of others different levels of the productive chain and also, the main strangulation points on these different levels of the productive chain. In the chapter 5 the agricultural process of the ginger benefit and cultivation in Morretes Town, Paraná, Brazil was caracterized. In the chapter 6 the hygienic-sanitary conditions of the producers establishments, postharvest benefit system and manipulation conditions of crude ginger in the paranaense coastland, Brazil were evaluated with an aim to subsidy the ofert of the best quality product to consumer market. In general, the cleaning and hygienic conditions were precarious, determining a high potential of ginger contamination with agents that can put in risk the consumers’ health. The chapter 7 presents the results of the commercialization establishments in the metropolitan area of Curitiba considering adequation to the current norm. Of the observed items, the manipulation conditions was considered precarious due to the inadequate conditions that contributes to contamination, bringing about serious problems to consumers’ health.The chapter 8 aimed the microbiological quality of the ginger market in the metropolitan area of Curitiba based on the Brazilian legislation. The microbiological analysis found total coliforms, 45° C/g coliforms, Escherichia coli most probable number (MPN) and Salmonella sp presence. Synthetizing, a group of considerations and recommendations to economic agents that actuate and carry on the productive chain of the ginger in the Parana State, specially in Morretes Town, is presented.